1986
DOI: 10.1113/jphysiol.1986.sp016215
|View full text |Cite
|
Sign up to set email alerts
|

A search for brain stem cell groups integrating the defence reaction in the rat.

Abstract: SUMMARY1. The defence areas of the rat brain stem have been extensively explored using electrical and chemical stimulation in an attempt to locate the regions containing the perikarya of neurones which may initiate or integrate the visceral and behavioural components of the defence reaction.2. In rats anaesthetized with alphaxalone-alphadolone, a cannula electrode was used to compare the responses to electrical stimuli with those evoked by microinjection of the excitatory amino acid D,L-homocysteic acid (DLH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
7
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(86 citation statements)
references
References 21 publications
5
73
7
1
Order By: Relevance
“…This response can be elicited in experimental animals by exposure to a rival or a predator and can be mimicked by electrical stimulation of the LH (Hilton, 1982) or chemical disinhibition of this region (Kayaba et al, 2003). The descending component of the defense reaction is thought to be mediated in part by neurons in the dorsomedial PAG (Hilton and Redfern, 1986). However, we found relatively few double-labeled neurons in this region, suggesting that this response may be mediated by a small number of cells.…”
Section: Functional Implicationscontrasting
confidence: 39%
See 1 more Smart Citation
“…This response can be elicited in experimental animals by exposure to a rival or a predator and can be mimicked by electrical stimulation of the LH (Hilton, 1982) or chemical disinhibition of this region (Kayaba et al, 2003). The descending component of the defense reaction is thought to be mediated in part by neurons in the dorsomedial PAG (Hilton and Redfern, 1986). However, we found relatively few double-labeled neurons in this region, suggesting that this response may be mediated by a small number of cells.…”
Section: Functional Implicationscontrasting
confidence: 39%
“…Several studies have examined the role that different brain regions may play in mediating behaviors that require concomitant activation of sympathetic and somatomotor efferent systems. In these studies, one or several brain regions were stimulated either electrically (Abrahams et al, 1960;Yardley and Hilton, 1986) or chemically with injections of excitatory amino acids (Bandler, 1982;Hilton and Redfern, 1986), and then behavioral, somatomotor, and autonomic parameters were simultaneously measured. Electrical stimulation has the potential to activate cell bodies as well as fibers of passage, thus complicating interpretation of observed effects.…”
Section: Introductionmentioning
confidence: 99%
“…The heart rate response was the most variable, bradycardia being probably due to the baroreflex activation. This excitatory haemodynamic reaction mimicked the one provoked by situations of stress or physical effort in conscious animals (Hilton & Redfern, 1986).…”
Section: Discussionmentioning
confidence: 58%
“…They also provided evidence that the descending pathway from the lateral hypothalamus was glutamatergic. This finding was contradicted by Hilton and Redfern as there was no sympathetic arousal as observed in the cardiovascular defensive response evoked by electrical or chemical stimulation of the hypothalamus (Hilton and Redfern, 1986). Furthermore, Hilton and associates demonstrated that sympathoexcitatory responses characteristic of the defence reaction were readily evoked by both electrical and chemical PAG stimulation (Hilton andRedfern, 1986, Yardley and.…”
Section: Hypothalamuscontrasting
confidence: 38%